Debating the Future of Biblical Archaeology - Corbett, Glenn J. (The Biblical archaeology review, 2024)
This past January, prominent archaeologists and biblical scholars from around the world gathered for a weekend of lectures and discussion at the Lanier Theological Library in Houston. The event, organized by Lipscomb University, was primarily a commemoration of the work and legacy of William Dever, the longtime leading voice of American biblical archaeology,a who celebrated […]